Effects of ultrasound-guided recruitment manoeuvres on postoperative pulmonary complications in laparoscopic bariatric surgery patients: study protocol for a randomised clinical trial - Yu-Qi Liao; Jin-Dong Yang; Yi He; Xin Tong; Jing Wen; Yan-Jun Liu; Qiang Fu (Trials)
Abstract Background Lung ultrasound-guided alveolar recruitment manoeuvres (RMs) may reduce the lung ultrasound score. However, whether the use of this strategy can reduce the incidence of postoperative pulmonary complications (PPCs) in the adult obese population has not yet been tested. Methods/design This is a single-centre, two-arm, prospective, randomised controlled trial. A total number of 476 obese patients scheduled for bariatric surgeries will be enrolled. They will be randomly assigned to receive either lung ultrasound-guided RMs (intervention group) or conventional RMs (control group) intraoperatively. The occurrence of PPCs will be recorded as the primary outcome. Discussion To the best of our knowledge, this is the first trial to test the effect of lung ultrasound-guided RMs on PPCs. The results of this trial will support the anaesthesiologists in choosing a potentially more efficient method to perform RMs for bariatric surgery patients. Trial registration www.chictr.org.cn ChiCTR2400080203. Registered on 23 January 2024.